Measuring trade integration in Africa - Bouët, Antoine; Cosnard, Lionel; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
In the Malabo Declaration of June 2014, African countries committed to tripling the level of intra-African agricultural trade and services by 2025, fast-tracking the establishment of a Continental Free Trade Area, and adopting a continentwide common external tariff. To accomplish these goals, African countries will need to consistently and accurately measure their participation in international trade. This paper reviews the literature on the measurement and qualification of trade integration in Africa. Starting with a complete review of available indicators and methodologies, it develops a methodological toolbox for better evaluation of the actual level of trade integration on the continent and formulates recommendations for policy assessment. It recommends use of a diverse range of indicators and methodologies, reviewing indicators that have recently emerged from network analysis and indicators of trade in value added. The study concludes that Africa is characterized by weak trade integration, particularly with the rest of the world. The region’s small number of trading partners and low product diversification are also striking. Contrary to what can be concluded from some simple trade share indicators, the use of more refined indicators shows that intra-African trade is relatively high compared with trade with other continents.